Longitudinal analysis of HIV-1 BF1 recombinant strains in vertically infected children from Argentina reveals a decrease in CRF12_BF pol gene mosaic patterns and high diversity of BF unique recombinant forms - Aulicino, Paula (2011)
The HIV-1 epidemic associated to BF1 recombinants in South America is both complex and intriguing, with an underestimated diversity of recombinant structures. Our aim was to explore the characteristics and temporal dynamics of the HIV-1 BF1 epidemic in Argentina, through the study of 172 HIV-1 pol BF1 recombinant sequences obtained from HIV-1 vertically infected patients born from 1986 to 2008. Recombination patterns were characterized by bootscanning, subtype signature analysis, and phylogenetic approaches. Proportion of sequences sharing common ancestry and recombination breakpoints with the Circulating Recombinant Form (CRF) CRF12_BF was compared against sequences with a non-CRF12_BF pattern in three study periods, and by fitting the data to a logistic model. Twenty-eight HIV-1 pol BF1 mosaic structures were identified, including four of the seven South-American CRF_BF-like patterns. However, common ancestry of these sequences with reference CRF strains only confirmed the presence of CRF12_BF (51.1%) and CRF17_BF (1.2%) among the Argentine BF pol sequences. Most non-CRF_BF-like recombinant patterns shared at least one common recombination breakpoint with CRF12_BF. The number of transmissions caused by CRF12_BF viruses decreased in a linear way over time, from 69% in the period 1986–1993 to 46% in 2001–2008. In conclusion, the diversity of HIV-1 pol BF1 recombinant structures in Argentina is much more complex than previously described, with at least two CRFs_BF and 26 BF1 unique recombinant forms. For the first time, we provide evidence of a decrease in the proportion of CRF12_BF viruses transmitted from mother-to-child since the start of the epidemic to the present time in Argentina.